Prospective evaluation of relationships between radiotherapy dose to masticatory apparatus and trismus. (3rd August 2018) - Hague, Christina; Beasley, William; Garcez, Kate; Lee, Lip W.; McPartlin, Andrew; McWilliam, Alan; Ryder, David; Sykes, Andrew J.; Thomson, David; van Herk, Marcel; West, Catharine; Slevin, Nick J.
Abstract: Aims: This feasibility study aimed to identify relationships between radiation doses to the masticatory apparatus as a combined block or as individual subunits with changes in trismus following radiotherapy. Material and methods: Twenty patients from a single center were recruited prospectively as part of a randomized trial comparing proactive exercises in the management of trismus. Patients with stage III/IV oral cavity or oropharyngeal squamous cell cancers received intensity-modulated radiotherapy with concurrent systemic therapy. All patients had trismus prior to radiotherapy. Maximal inter-incisor distance (MID) was measured pre- and 6 months from the start of radiotherapy. Bilateral muscles of mastication: medial and lateral pterygoids (MP and LP), masseters (M), temporalis (T), temporomandibular joint (TMJ) were contoured on CT images. The block comprised all muscles excluding the TMJ below the orbital floor. Mean dose, equivalent uniform dose (EUD) and V35–V60 Gy were compared with change in MID. Results: In six patients, the MID deteriorated at 6 months from the start of radiotherapy compared with 14 whose MID improved. No significant association was observed between age, gender, smoking, alcohol status, exercise compliance, cisplatin, tumor site, stage, V35–V60 Gy or EUD with change in MID. A clinical outlier was excluded. Without the outlier ( n  = 19), a significant association was seen between mean dose and change in MID at 6 months for the ipsilateral block ( p  = .01), LP ( p  = .04) and M ( p  < .01). All patients where trismus deteriorated at 6 months received mean doses >40 Gy to the block. Conclusion: Higher mean radiation doses to the ipsilateral block, LP and M were significantly associated with deterioration in trismus. Limiting dose to these structures to ≤40 Gy for tumors not invading the masticatory muscles may improve treatment-related sequelae. The ipsilateral block, LP and M should be studied further as possible alternative avoidance structures in radiotherapy treatment planning.